KEANEKARAGAMAN JENIS VEGETASI POHON HUTAN ADAT GUNUNG SEMARONG DI DESA MANDONG KECAMATAN TAYAN HULU KABUPATEN SANGGAU TREE DIVERSITY IN MOUNT SEMARONG CUSTOMARY FOREST MANDONG VILLAGE TAYAN HULU SUBDISTRICT SANGGAU REGENCY - Bayu P, Lidwinus Christo; Manurung, Togar Fernando; dina, Wah (Universitas Tanjungpura, 2014)
This study aims to determine the level of tree species diversity in the forest vegetation of Mountain Semarong customary forest, one of the lowland secondary forest that have potential to be developed as research and education forest. Data and information about the vegetation include tree species composition and structure in the forest is needed.This study is done in four weeks, using transect method with random 10 lines 500 m length eachand each line consist of Â 25 plots 1 ha each.The tree vegetation in Mount Semarong customary forest consist ofÂ 42 spesies of Â 23 families. The highest important value index as for durian(Durio zibethinus) famili Malvaceae, mentawa (Artocarpus anisophyllus) famili Moraceae, ubah arang (Syzygium acumminatissium) famili Myrtaceae, dan kemayan (Sytrax sp) famili Sytraxcaceae and the lowest one as for angkaras(Aquilaria malaccensis) famili Thymeleaceae. It is also known that there is a kind of economic value such as durian (Durio zibethinus), kepuak (Artocarpus elasticus), meranti (Shorea sp), tengkawang tungkul (Shorea macrophylla), Pulai (Alstonia scholaris), awat'n (Cratoxylum sp), and angkaras (Aquilaria malaccensis). According to the endegered IUCN Red List report on the species found in the category of endangered, critically, and vulnerable, namely Alstonia scholaris, Shorea sp, Cratoxylum sp, and Aquilaria malaccensis. The composition of trees in a Mount Semarong forest have a low dominance index (0.0537), Species Diversity Index has a value of 0.9643 index which shows high species diversity in the region. From another standpoint, Mount Semarong customary forest very likely to be developed for the source of life, education, and culture. Keywords : Diversity, tree vegetation, and IUCN